Comparative Genomic Analysis of Holospora spp., Intranuclear Symbionts of Paramecia - Garushyants, Sofya K.; Beliavskaia, Alexandra Y.; Malko, Dmitry B.; Logacheva, Maria D.; Rautian, Maria S.; Gelfand, Mikhail S. (Frontiers in Microbiology, 2018)
While most endosymbiotic bacteria are transmitted only vertically, Holospora spp., an alphaproteobacterium from the Rickettsiales order, can desert its host and invade a new one. All bacteria from the genus Holospora are intranuclear symbionts of ciliates Paramecium spp. with strict species and nuclear specificity. Comparative metabolic reconstruction based on the newly-sequenced genome of Holospora curviuscula, a macronuclear symbiont of Paramecium bursaria, and known genomes of other Holospora species shows that even though all Holospora spp. can persist outside the host, they cannot synthesize most of the essential small molecules, such as amino acids, and lack some central energy metabolic pathways, including glycolysis and the citric acid cycle. As the main energy source, Holospora spp. likely rely on nucleotides pirated from the host. Holospora-specific genes absent from other Rickettsiales are possibly involved in the lifestyle switch from the infectious to the reproductive form and in cell invasion.